Effect of BMITFSI to the Electrical Properties of Methylcellulose/Chitosan/NH4TF Based Polymer Electrolyte - Ariffin, NA; Khiar, ASA (Spie-Int Soc Optical Engineering, 2024)
Blended polymer electrolyte of methylcellulose (MC) / chitosan with ammonium triflate (NH4TF) were prepared with different weight percentage of 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl) imide (BMITFSI) via solution casting technique. The film was characterized by impedance spectroscopy to measure its ionic conductivity. Samples with 45% of BMITFSI exhibit the highest conductivity of (3.98 +/- 2.84) x 10(-4) Scm(-1) at ambient. Dielectric data were analyzed by using complex permittivity and complex electrical modulus for the sample with highest conductivity. Dielectric data proves that the increase in conductivity is mainly due to the increase in number of charge carriers.